ABCA7 Genotypes Confer Alzheimer's Disease Risk by Modulating Amyloid-β Pathology. - Zhao, Qing-Fei; Wan, Yu; Wang, Hui-Fu; Sun, Fu-Rong; Hao, Xiao-Ke; Tan, Meng-Shan; Tan, Chen-Chen; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
ABCA7 gene has been identified as a strong genetic locus for Alzheimer's disease (AD) susceptibility in genome wide association studies (GWAS). However, the possible roles of ABCA7 variants in AD pathology were not specifically assessed. Using tagger methods, we extracted 15 targeted ABCA7 loci to investigate their associations with cerebrospinal fluid (CSF) and neuroimaging markers in Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. Finally, although we did not detect any significant associations of previously published GWAS SNPs (rs3764650 and rs78117248) with all the CSF (Aβ1 - 42, T-tau, and P-tau) and neuroimaging markers, three other variants (rs3752242, rs3752240, and rs4147912) at ABCA7 loci were detected to show significant associations with amyloid deposition on AV-45 PET in brain. Moreover, haplotype and subgroup analysis confirmed these significant findings. Furthermore, there were no remarkable correlations between ABCA7 variants and neuronal degeneration biomarkers (elevated CSF tau, brain structure atrophy, and hypometabolism on imaging) in this study. Thus, our study suggested that ABCA7 genotypes contribute to the AD risk through involvement in amyloid-β deposition on in vivo imaging, but not in tau pathology, brain atrophy, or decreased glucose metabolism.